IMPLEMENTASI PEMBELAJARAN NAWA WIDHA BHAKTI DALAM PEMBENTUKAN KARAKTER RELIGIUS SISWA DI SEKOLAH MENENGAH KEJURUAN NEGERI 1 DENPASAR - I Wayan Agus Juliawan (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2026)
This study investigates the implementation of Nawa Widha Bhakti in fostering students' religious character through Hindu Religious Education at SMK Negeri 1 Denpasar. The research focuses on three aspects: the implementation process, the factors influencing its effectiveness, and teachers' strategies for strengthening the religious character of students who have not yet fully internalized these values. A qualitative approach with a phenomenological design was employed. Data were collected through non-participant observation, in-depth interviews, documentation, and library research involving the principal, Hindu Religious Education teachers, and Grade XI students selected through purposive sampling. The analysis was guided by Abraham Maslow's Humanistic Theory, Thomas Lickona's Character Education Theory, and Robert M. Gagné's Meaningful Learning Theory. The findings reveal that the values of Nawa Widha Bhakti have been integrated into the Merdeka Curriculum and daily school practices, including Sravanam (listening to sacred teachings), Vandanam (prayer), and Padasevanam (selfless service). Successful implementation is supported by strong school leadership, teachers' exemplary conduct, and adequate worship facilities, while challenges stem from external social influences and limited personal awareness among some students. Teachers address these challenges through a humanistic approach, reflective dialogue, and the continuous integration of meaningful learning experiences.